PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN INDIHOME PADA PT TELKOM AKSES DI JOHAR BARU JAKARTA PUSAT - Azmi Ramadhan, Muhammad; Kumara, Dedek (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the partial or simultaneous influence of Service Quality and Price on Indihome Customer Satisfaction at PT Telkom Akses in Johar Baru, Central Jakarta. The research method used is an associative quantitative method. Data processing is quantitative using SPSS software version 26. The population with a total of 435,300 and the sample in this study were Indihome respondents, determining the number of samples using the slovin method obtained 99.97 respondents and the number was rounded up to 100 respondents, by collecting data using a questionnaire given to respondents, the data collection method using incidental sampling. In this study, the data collection techniques used were observation, questionnaires, literature studies, and documentation. That this study was conducted using data analysis, namely descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, simultaneous f hypothesis test, partial t hypothesis test. Statistical tests on independent variables are service quality and price while the dependent variable is customer satisfaction. All statements are valid, reliable, and normal, based on the tests conducted, the results of this study indicate that the regression coefficient value can be seen that the service quality variable (X1) is 0.323, the price variable (X2) is 0.289, service quality and price have a strong relationship to customer satisfaction can be seen in the R Square of 0.528, which shows that the independent variables consisting of service quality and price can be explained by customer satisfaction of 52.8% are able to explain the dependent variable, namely customer satisfaction (Y) while the remaining 47.2% are influenced by other variables not examined in this study. In the service quality variable, the calculated t value is obtained> t table or (4.348> 1.660) thus H0 is rejected and H1 is accepted, in the price variable the calculated t value is obtained> t table (4.492> 1.660) thus H0 is rejected and H2 is accepted. Simultaneously, the variables of service quality (X1) and price (X2) have a positive and significant effect on customer satisfaction (Y). This is shown from the results of the calculation of the calculated F value > F table or (54.298 > 3.09). The conclusion of this study is that service quality and price have a positive and significant effect on customer satisfaction.